Shock Wave Therapy Enhances Mitochondrial Delivery into Target Cells and Protects against Acute Respiratory Distress Syndrome - Lin, Kun-Chen; Wallace, Christopher Glenn; Yin, Tsung-Cheng; Sung, Pei-Hsun; Chen, Kuan-Hung; Lu, Hung-I; Chai, Han-Tan; Chen, Chih-Hung; Chen, Yi-Ling; Li, Yi-Chen; Shao, Pei-Lin; Lee, Mel S.; et al. (Mediators of Inflammation, 2018)
This study tested the hypothesis that shock wave therapy (SW) enhances mitochondrial uptake into the lung epithelial and parenchymal cells to attenuate lung injury from acute respiratory distress syndrome (ARDS). ARDS was induced in rats through continuous inhalation of 100% oxygen for 48 h, while SW entailed application 0.15 mJ/mm2 for 200 impulses at 6 Hz per left/right lung field. In vitro and ex vivo studies showed that SW enhances mitochondrial uptake into lung epithelial and parenchyma cells (all p<0.001). Flow cytometry demonstrated that albumin levels and numbers of inflammatory cells (Ly6G+/CD14+/CD68+/CD11b/c+) in bronchoalveolar lavage fluid were the highest in untreated ARDS, were progressively reduced across SW, Mito, and SW + Mito (all p<0.0001), and were the lowest in sham controls. The same profile was also seen for fibrosis/collagen deposition, levels of biomarkers of oxidative stress (NOX-1/NOX-2/oxidized protein), inflammation (MMP-9/TNF-α/NF-κB/IL-1β/ICAM-1), apoptosis (cleaved caspase 3/PARP), fibrosis (Smad3/TGF-β), mitochondrial damage (cytosolic cytochrome c) (all p<0.0001), and DNA damage (γ-H2AX+), and numbers of parenchymal inflammatory cells (CD11+/CD14+/CD40L+/F4/80+) (p<0.0001). These results suggest that SW-assisted Mito therapy effectively protects the lung parenchyma from ARDS-induced injury.